1981
DOI: 10.1056/nejm198103053041001
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous MZ Alpha1-Antitrypsin Deficiency in Adults with Chronic Active Hepatitis and Cryptogenic Cirrhosis

Abstract: To determine the prevalence of alpha 1-antitrypsin deficiency in patients with cirrhosis or chronic active hepatitis, we performed a five-year prospective study of liver-biopsy specimens from 1055 adults. Thirty-four patients whose specimens contained hepatocyte inclusions characteristic of the deficiency were phenotyped, and 25 had phenotype MZ (2.4 per cent). The distribution of patients with this phenotype among the 185 patients with cirrhosis diagnosed histologically was three of 84 patients with alcoholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(68 citation statements)
references
References 23 publications
2
65
1
Order By: Relevance
“…Besides taking a hepatotoxic weight-loss supplement, our patient was also heterozygous for alpha-1 antitrypsin deficiency. There remains considerable debate regarding the importance of the alpha-1 antitrypsin MZ phenotype [11,[17][18][19][20][21] . Graziadei et al [17] suggested that the alpha-1 antitrypsin MZ phenotype might be a risk factor for chronic liver disease or liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Besides taking a hepatotoxic weight-loss supplement, our patient was also heterozygous for alpha-1 antitrypsin deficiency. There remains considerable debate regarding the importance of the alpha-1 antitrypsin MZ phenotype [11,[17][18][19][20][21] . Graziadei et al [17] suggested that the alpha-1 antitrypsin MZ phenotype might be a risk factor for chronic liver disease or liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…There is no increased risk of emphysema. However, there is evidence linking these heterozygous states to cryptogenic cirrhosis (11)(12)(13). In one study, 2.4% of 1,055 adults who were undergoing liver biopsy had the MZ phenotype (12).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a1AT*ZZ individuals who smoke exhibit a rapid onset of emphysema, often by 30 years of age, and death by the age of 50. 15 However, most a1AT*ZZ individuals who avoid smoking live normal length lives with minimal complications. Replacement therapy for a1AT deficiency, with intravenous a1AT from pooled human plasma, results in longer survival.…”
mentioning
confidence: 99%